Research on Data Transmission Optimization Of Communication Network Based on Reliability Analysis - Wang, Hui (Informatica, 2020)
This paper briefly introduced the vehicular communication network, vehicular ad-hoc network (VANET), and the ant colony algorithm for path search in the network, improved the ant colony algorithm, carried out a simulation experiment on the improved ant colony algorithm on the simulation platform, and compared it with the traditional ant colony algorithm and the geographical location-based routing algorithm. The results showed that the network packet loss rate and time delay showed a tendency of increasing first and then decreasing under the three algorithms with the increase of vehicle nodes in VANET; with the increase of nodes, the network reliability under the improved ant colony algorithm showed a tendency of increasing first and then being stable, and the network reliability under the other two algorithms showed a tendency of increasing first and then decreasing; under the same number of nodes, the packet loss rate and average delay were lower, and the reliability was higher under the improved ant colony algorithm.